2019
DOI: 10.1111/ajd.13004
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of partial biopsies in the management of cutaneous melanoma

Abstract: Background: The recommended method for histopathological diagnosis of cutaneous melanoma is excisional biopsy, although partial biopsies (shave and punch) are often used. Following a partial biopsy, treatment guidelines recommend a narrow excisional biopsy to plan definitive management. There is limited evidence on the benefits of direct wide local excision (WLE) following diagnostic partial biopsies.Methods: Retrospective cohort study of cutaneous melanoma cases, from two tertiary referral centres from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…It is also the strongest prognostic indicator for patients with localized cutaneous melanoma. 6,26 Many international and national guidelines recommend excision biopsy as the preferred mode for biopsy of suspicious pigmented skin lesions because it allows for examination of the entire lesion and therefore provides the most accurate measurement of true Breslow thickness. 3,[28][29][30] Additional treatments following a melanoma diagnosis include WLE and SLNB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also the strongest prognostic indicator for patients with localized cutaneous melanoma. 6,26 Many international and national guidelines recommend excision biopsy as the preferred mode for biopsy of suspicious pigmented skin lesions because it allows for examination of the entire lesion and therefore provides the most accurate measurement of true Breslow thickness. 3,[28][29][30] Additional treatments following a melanoma diagnosis include WLE and SLNB.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of lesion thickness on deep margin status, Doolan et al, in a study of 455 patients, further reported that the rate of deep margin positivity increased from 48% for those with melanomas \1 mm in Breslow thickness, to 90% in those with Breslow thickness [2 mm. 26 High heterogeneity was observed across studies (I 2 = 98.9%).…”
Section: Deep Margin Statusmentioning
confidence: 97%
See 3 more Smart Citations